2002
DOI: 10.1016/s0885-3924(02)00417-7
|View full text |Cite
|
Sign up to set email alerts
|

Family Satisfaction with End-of-Life Care for Cancer Patients in a Cluster Randomized Trial

Abstract: The main aim of this study was to examine similarities and differences in satisfaction with care between 112 family members who were close to patients who had participated in an intervention with a comprehensive palliative care program and the 68 family members in a conventional care program (controls). The FAMCARE Scale measured satisfaction with care at one month after the time of death. The majority of respondents reported high satisfaction with care. The respondents related to the patients in the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
4
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 33 publications
(42 reference statements)
8
113
4
7
Order By: Relevance
“…Our study lends support to this assumption. Unlike other studies (Medigovich et al, 1999;Ringdal, Jordhøy, Kaasa, 2002;Can et al, 2011) we did not find significant differences between genders. The group of men in our study had a slightly higher satisfaction rate than the group of women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study lends support to this assumption. Unlike other studies (Medigovich et al, 1999;Ringdal, Jordhøy, Kaasa, 2002;Can et al, 2011) we did not find significant differences between genders. The group of men in our study had a slightly higher satisfaction rate than the group of women.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the sociodemographic characteristics, the group of middle-aged family caregivers (51 to 65 years) showed the lowest level of satisfaction in the overall FAMCARE-2 score, and in all dimensions, except dimension 3: "Family support", whereas the group with the oldest family caregivers (66 or older), had the highest satisfaction in this sample. This high satisfaction of older family caregivers has been observed in many other studies worldwide (Medigovich et al, 1999;Smith, 2000;Ringdal, Jordhøy, Kaasa, 2002;Can et al, 2011). One explanation for this phenomenon could be that older family caregivers who take responsibility for other older family members rated the service more positively than caregivers of younger family members (Kristjanson, 1993;Medigovich et al, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…Early studies demonstrated clear benefit from palliative care expertise in management of pain and other symptoms associated with advanced illness, supporting caregivers, coordinating communication, and medical decision-making between clinical teams and patient/family unit, and providing comfort at end-of-life [4][5][6].…”
Section: Originsmentioning
confidence: 99%
“…22,[29][30][31][32][33][34][35][36][37][38][39] Treatment of distressing symptoms by interdisciplinary palliative care and hospice teams translates to reduced medical complications and hospital utilization. 12,13,[40][41][42] In addition to symptom management, palliative care providers have expertise in the conduct of conversations with patients and families dedicated to assuring understanding of what to expect in the future, including prognosis and the resulting goals of care.…”
Section: Palliative Care and Hospicementioning
confidence: 99%